Jewish-Christian gospel tradition - Klijn, Albertus Frederik Johannes. (Vigiliae Christianae, Supplements, 1992)
This work represents the first independent study of the Jewish-Christian Gospel fragments and of the use of the Jewish-Christian Gospel tradition in early Christian and medieval literature. The author identifies and introduces the Jewish-Christian Gospels and their sources, presents a critical study of genuine and spurious references to Jewish-Christian Gospels, and then goes on to offer a critical text (with apparatus and bibliography), a translation and a full commentary for each individual fragment.